Low-frequency internal friction (LFIF) as express method for identification of cryocrystals in pores of the solids - Leont’eva, A.V.; Erenburg, A.I.; Prokhorov, A.Yu. (Recent Contributions to Physics, 2015)
Cryocrystals (solidified gases) form a relatively small group of materials which are gaseous at room temperatures and solids at low ones. They have the triple points at low temperatures because of low weight and small size of their molecules and also weakness of binding forces. This group of solids includes atomic cryocrystals (He, Ne, Ar, Kr, Xe), simplest molecular crystals (hydrogen, nitrogen, CO, oxygen, fluorine), and also few crystals from bigger molecules (CO2, N2O, CH4, NH3 etc.). Being chemically neutral, the gases fill the pores and becomes cryocrystals under cooling, influencing the properties of the solid matrices.